Dynamic Inventions - Schipper, Alexander (Auckland University of Technology, 2018)
Dynamic Inventions is a practice-based art project about identity. It manifests itself via reflexive video installations that address its questions and concerns by immersing them in the dynamic of my exploratory process as I work to unfold my own identity. It is through this reflexive art-making process that I examine the terms of my question: What might constitute identity? That is, how does identity relate to certain properties or qualities and how might these qualities be essential to identity, and how might they be revealed or represented through art? What the project reveals is that if the subject of investigation is living, growing and continually changing, in part through conducting this project, identity then is not fixed nor is it located in some essential quality, but is contingent, complex, relational and in continual change. Furthermore, a conception of identity is as much a perception from outside as it is a conception from within the subject. What started as an investigation of identity has shifted to being a project about identity that is a process of becoming-being. This process is life-long, so the question of determining identity becomes inappropriate, and redundant. What remains is the question, How am I becoming me?
Keywords: Video art; Video installation art; Reflexive; Process; Identity